Assessment of the frequency, severity and causes of urethral complications after transurethral resection surgery (Literature Review) (Eurasian Medical Research Periodical, 2024)
Lower urinary tract symptoms secondary to benign prostatic hyperplasia (prostate adenoma) are more common in older men and have a greater than 50% chance of developing the disease in men over 60 years of age[1]. Transurethral resection of the prostate (Turp), defined as the "gold standard" of surgical treatment of prostate adenoma recommended by the American Urological Association (AUA), is minimally invasive[2]. Insertion of a three-sided catheter after transurethral resection was standard practice to prevent bleeding caused by emptying the bladder. Urologists usually remove the catheter, allowing patients to attempt to urinate on their own. [5] the urethra is the second most important factor after traumatic urethral injury due to an increase in the number of transurethral interventions and catheterization and is a leading factor in the development of urethral structures